Pengaruh Multi Level Marketing Terhadap Penjualan Produk Serum Vitamin C Salisa - Effendi, Wiranto J. C; Kalangi, Johnny A. F.; Mukuan, Danny D. S. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The purpose of this study was to examine the effect of Multilevel Marketing on the sale of Serim Vitamin C Salisa. Cosmetics has become one of the human needs in general. One of the cosmetics companies that saw this opportunity and marketed its products in Indonesia, namely PT. Aura Cantik Indonesia. This type of research is quantitative research. The data validity test results obtained all items in question declared valid. Furthermore, Anova output above is known that the calculated F value = 744,645 with a significance of 0,000 <0.05 then the regression model can be used to predict Multi-Level Marketing (X) variables or in other words, there are the influence of Multi-Level Marketing (X) variables on Sales variables ( Y). Furthermore, the results of the Determination Coefficient Test, R Square of 88.5% which states that the variable Sales of Vitamin C Salisa (Y) Serum Products is influenced by the Multi-Level Marketing (X) influence variable, while the remaining 11.5% is influenced by other variables that are not in this study.